A Yaw Rate Tracking Control of Active Front Steering System Using Composite Nonlinear Feedback - Muhamad Khairi, Aripin; Y.M, Sam; Kumeresan, A.D; Kemao , Peng; Mohd Hanif , Che Hasan; Muhamad Fahezal, Ismail (Springer Berlin Heidelberg, 2013)
In this paper, the composite nonlinear feedback (CNF) technique is applied for yaw tracking control of active front steering system with the objectives to improve the transient performance of yaw rate response. For lateral and yaw dynamics analysis, nonlinear and linear vehicle models are utilized as actual vehicle plant and for controller design respectively. The designed controller is evaluated using J-turn cornering manoeuvre condition in computer simulation. The simulation results demonstrate that the application of CNF for yaw rate tracking control improves the yaw stability and vehicle handling performances.